2020
DOI: 10.21203/rs.3.rs-33047/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lack of Benefit in COVID-19 Patients Treated with Hydroxychloroquine or Chloroquine: A Systematic Review and Meta-Analysis

Abstract: Background: Hydroxychloroquine (HCQ) and chloroquine (CQ) have been widely used for the treatment of the coronavirus disease 2019 (COVID-19), despite limited clinical evidence and controversial early reports. The aim of this report was to provide a systematic review of the literature and meta-analysis on the use of HCQ/CQ with respect to safety and clinical efficacy of these medications. Methods: We performed a systematic search of the medical databases and included studies if they focused on patients with COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…For instance, recently, an observational cohort study proposed that HCQ, either alone or in combination with azithromycin, had not a survival advantage among hospitalized patients with COVID-19 [109]. Another meta-analysis also revealed that the administration of HCQ/CQ had not any considerable impacts on SARS-CoV-2 clearance and even increased hospitalized patients with COVID-19 mortality with a higher risk in COVID-19 patients with comorbidities [110]. In a randomized investigation from China, in patients with a mild to moderate SARS-CoV-2 infection recovery rates was not valuable following HCQ therapy [107].…”
Section: Hydroxychloroquine (Hcq)mentioning
confidence: 99%
“…For instance, recently, an observational cohort study proposed that HCQ, either alone or in combination with azithromycin, had not a survival advantage among hospitalized patients with COVID-19 [109]. Another meta-analysis also revealed that the administration of HCQ/CQ had not any considerable impacts on SARS-CoV-2 clearance and even increased hospitalized patients with COVID-19 mortality with a higher risk in COVID-19 patients with comorbidities [110]. In a randomized investigation from China, in patients with a mild to moderate SARS-CoV-2 infection recovery rates was not valuable following HCQ therapy [107].…”
Section: Hydroxychloroquine (Hcq)mentioning
confidence: 99%